Regional integration in West Africa : is there a role for a single currency? - Prasad, Eswar; Songwe, Vera (Brookings Institution Press, 2021)
"Leaders of the fifteen-member Economic Community of West African States (ECOWAS) had set a goal of achieving a monetary and currency union by late 2020. The COVID pandemic and the lack of macroeconomic convergence among member countries precipitated a postponement of this goal. As this book shows, a currency union could offer many potential benefits but would also come with significant costs, along with operational challenges and transitional risks. This book, by two leading experts on economics and Africa, makes a major analytical contribution to the debates now under way about how ECOWAS could achieve greater trade and financial integration, with or without a currency union, and the ramifications for the African continent."--